2016
DOI: 10.2216/15-149.1
|View full text |Cite
|
Sign up to set email alerts
|

Limnolyngbya circumcreta gen.&comb. nov. (Synechococcales, Cyanobacteria) with three geographical (provincial) genotypes in China

Abstract: Five strains that were morphologically identified as Planktolyngbya circumcreta were isolated from three geographical regions in China. The strains were phylogenetically and taxonomically characterised based on a polyphasic approach that merged morphological and genetic characteristics, as well as ultrastructure. The ultrastructure of these strains showed a similar arrangement of thylakoids, with four to eight parallel layers that were parietally distributed, suggesting that they belonged to the order Synechoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…In 2009, studies on marine cyanobacteria by Bily et al [48] showed that Synechococcus elongatus could store excess phosphate and synthesize polyphosphate particles in the cytoplasm or vacuoles to remove phosphorus in the water. Multiple groups of Synechococcales were observed with transmission electron microscopy to relate to polyP particles found in bacterial cells [49,50], confirming that Synechococcales stored polyP in response to phosphorus limitation in the environment [51].…”
Section: Discussionmentioning
confidence: 72%
“…In 2009, studies on marine cyanobacteria by Bily et al [48] showed that Synechococcus elongatus could store excess phosphate and synthesize polyphosphate particles in the cytoplasm or vacuoles to remove phosphorus in the water. Multiple groups of Synechococcales were observed with transmission electron microscopy to relate to polyP particles found in bacterial cells [49,50], confirming that Synechococcales stored polyP in response to phosphorus limitation in the environment [51].…”
Section: Discussionmentioning
confidence: 72%
“…The Synechococcales contains a great number of molecularly and morphologically divergent taxa. Seventy-four genera were recognized in the order in the newest taxonomic system (Komárek et al 2014), with (counting Lagosinema) 18 additional genera being published since that treatment (Dvořák et al 2015;Song et al 2015;Vaz et al 2015;Li & Li 2016;Miscoe et al 2016;Sciuto & Moro 2016;Dvořak et al 2017;Jahodářová et al 2017aJahodářová et al , 2017bSciuto et al 2017;Mai et al 2018). Furthermore, there are numerous unnamed or incorrectly named sequenced species that appear in our Science for the Developing World (OWSD) and the Swedish International Development Cooperation Agency (Sida) postgraduate training fellowship to Sandra C. Akagha (Grant No.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of genetic and morphological studies have been conducted to date, with a focus on the taxonomy of Leptolyngbyaceae (e.g., [29,30,35,36]). Li & Li [35] transferred five strains of Planktolyngbya circumcreta to the new genus Limnolyngbya within the Leptolyngbyaceae family. However, within this family, the general systematic patterns of the genera have yet to be clarified.…”
Section: Introductionmentioning
confidence: 99%